Population Pharmacokinetic Analysis of Voriconazole and Anidulafungin in Adult Patients with Invasive Aspergillosis - Liu, Ping (American Society for Microbiology, 2014)
To assess the pharmacokinetics (PK) of voriconazole and anidulafungin in patients with invasive aspergillosis (IA) in comparison with other populations, sparse PK data were obtained for 305 adults from a prospective phase 3 study comparing voriconazole and anidulafungin in combination versus voriconazole monotherapy (voriconazole, 6 mg/kg intravenously [IV] every 12 h [q12h] for 24 h followed by 4 mg/kg IV q12h, switched to 300 mg orally q12h as appropriate; with placebo or anidulafungin IV, a 200-mg loading dose followed by 100 mg q24h). Voriconazole PK was described by a two-compartment model with first-order absorption and mixed linear and time-dependent nonlinear (Michaelis-Menten) elimination; anidulafungin PK was described by a two-compartment model with first-order elimination. For voriconazole, the normal inverse Wishart prior approach was implemented to stabilize the model. Compared to previous models, no new covariates were identified for voriconazole or anidulafungin. PK parameter estimates of voriconazole and anidulafungin are in agreement with those reported previously except for voriconazole clearance (the nonlinear clearance component became minimal). At a 4-mg/kg IV dose, voriconazole exposure tended to increase slightly as age, weight, or body mass index increased, but the difference was not considered clinically relevant. Estimated voriconazole exposures in IA patients at 4 mg/kg IV were higher than those reported for healthy adults (e.g., the average area under the curve over a 12-hour dosing interval [AUC(0–12)] at steady state was 46% higher); while it is not definitive, age and concomitant medications may impact this difference. Estimated anidulafungin exposures in IA patients were comparable to those reported for the general patient population. This study was approved by the appropriate institutional review boards or ethics committees and registered on ClinicalTrials.gov (NCT00531479).